The relationship between perceived group based performance appraisal and social loafing and the moderating role of task visibility - Buz, Ertuğrul (My University, 2011)
Bu çalışmanın amacı, grup-odaklı performans değerleme algısının, iş arkadaşı sosyal kaytarma algısı üzerindeki etkisini incelemektir. Ayrıca, algısal görev görünürlüğünün grup-odaklı performans değerleme algısı ile iş arkadaşı sosyal kaytarma algısı arasındaki ilişki üzerinde şartlı değişken etkisinin olup olmadığı da araştırılmıştır. Buna ek olarak, demografik özellikler ile iş arkadaşı sosyal kaytarma algısı arasındaki ilişkiler de incelenmiştir. Araştırma modeli İstanbul’daki farklı özel kuruluşlarda takım halinde çalışan 151 katılımcı ile test edilmiştir. Araştırma anketi, algısal görev görünürlüğü, iş arkadaşı sosyal kaytarma algısı, grup-odaklı performans değerleme algısı ve demografik özellikleri içeren dört bölümden oluşmaktadır. Toplanan verilerin analizi SPSS 15 paket programıyla yapılmıştır. Elde edilen sonuçlara göre; grup-odaklı performans değerleme algısının, iş arkadaşı sosyal kaytarma algısı üzerinde pozitif bir katkısı vardır. Algılanan görev görünürlüğünün bu ilişkiye şartlı değişken olarak etki edip etmediği de araştırılmıştır. Bulunan sonuçlara göre; düşük görev görünürlüğü olan çalışma gruplarında, grup-odaklı performans değerleme algısının, iş arkadaşı sosyal kaytarma algısı üzerinde pozitif bir katkısı vardır, ancak görev görünürlüğü yüksek olan çalışma gruplarında bu katkı anlamsız bir hale dönüşmektedir. Başka bir, deyişle, yüksek görev görünürlüğü olan durumlarda bu katkı ortadan kalkmıştır.

The objective of this study was to investigate the contribution of perceived group-based performance appraisal on perceived co-worker social loafing. Besides, perceived task visibility was examined in terms of its moderating effect on the relationship between perceived group-based performance appraisal and perceived co-worker social loafing. Moreover, the relations between demographic characteristics and perceived co-worker social loafing were explored. The research model was tested with 151 participants working as a team at different private organizations in İstanbul, Turkey. The survey consisted of four sections including perceived task visibility, perceived co-worker social loafing, perceived group-based performance appraisal, and demographic characteristics. SPSS 15.0 program was used to conduct the statistical analysis of the data. The findings of the research indicated that perceived group-based performance appraisal had a positive contribution on perceived co-worker social loafing. The moderating effect of perceived task visibility on this relationship was also investigated and the results showed that there was a positive contribution of perceived group-based performance appraisal on perceived co-worker social loafing in work groups with low task visibility. However, in work groups with high task visibility, the contribution of perceived group-based performance appraisal on perceived co-worker social loafing became insignificant. In other words, this contribution disappeared in the high task visibility condition.
Keywords: Örgütsel Davranış; Performans Değerleme